Temporomandibular disorders and eating disorders: a literature review - Aroucha,João M. C. N. L. (2014)
INTRODUCTION: Temporomandibular disorders (TMD) and eating disorders (ED) affect function and parafunction of the oral cavity and have high rates of medical and psychological comorbidity. However, little is known about the possible associations between them, and few studies have investigated the existence of such associations. METHODS: A search was conducted on the SciELO, LILACS, and PubMed/MEDLINE databases to find relevant articles written in English and Portuguese. Only studies involving human beings were included, and there was no limit for year of publication. RESULTS AND CONCLUSIONS: There is evidence of the correlation between TMD and ED, but their comorbidity must be better understood. The presence of depressive symptoms is an aggravating factor that must also be taken into account during the diagnosis and treatment of those patients.